Trusted execution, and the impact of security on performance - Brenner, Stefan; Behlendorf, Michael; Kapitza, Rüdiger (Proceedings of the ACM Conference on Computer and Communications Security, 2018)
Due to increasing success of cloud computing offerings, the demand for sensitive data processing and security in the cloud has also increased. By incorporation of trusted execution technologies such as the broadly available Intel Software Guard Extensions (SGX), applications can be secured. However, software engineers need to align the development process with the capabilities and properties of such a technology, in order to correctly secure applications while achieving good performance. In this paper, we identify relevant aspects for partitioning applications and discuss two complementary designs optimising for performance or security respectively. Additionally, our contribution comprises a performance and security measurement, at the example of two established real-world applications, that we both partitioned according to the above two distinct design approaches. We consider this paper as a guideline for the partitioning process of mainly data-handling services for usage of trusted execution and as a collection of relevant characteristics during the development of applications with trusted execution environments.
CRIS-Team Scopus Importer:2022-07-19
Keywords: Application partitioning; Intel SGX